2020
DOI: 10.3390/jcm9030759
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Cervical Myelopathy: How to Identify the Best Responders to Surgery?

Abstract: Surgery is the only definitive treatment for degenerative cervical myelopathy (DCM), however, the degree of neurological recovery is often unpredictable. Here, we assess the utility of a multidimensional diagnostic approach, consisting of clinical, neurophysiological, and radiological parameters, to identify patients likely to benefit most from surgery. Thirty-six consecutive patients were prospectively analyzed using the modified Japanese Orthopedic Association (mJOA) score, MEPs/SSEPs and advance and convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The patients with severe DCM, who presented a higher FA value at the compressed level, were most likely to achieve a better functional recovery after decompression surgery [37]. This might identify FA as a potential positive predicting factor of postoperative outcomes: Therefore, DTI could be considered not only a complementary diagnostic analysis, but rather a crucial tool in order to identify the best candidates to surgery [38].…”
Section: Discussionmentioning
confidence: 99%
“…The patients with severe DCM, who presented a higher FA value at the compressed level, were most likely to achieve a better functional recovery after decompression surgery [37]. This might identify FA as a potential positive predicting factor of postoperative outcomes: Therefore, DTI could be considered not only a complementary diagnostic analysis, but rather a crucial tool in order to identify the best candidates to surgery [38].…”
Section: Discussionmentioning
confidence: 99%
“…The length of T2WI hyperintensity and the presence of T1 hypointensity have been related with worse baseline neurological severity and the presence of clinical signs and symptoms (18). There is also evidence that both T2WI hyperintensity length and T1 hypointensity are predictive of surgical outcome, while the presence or absence of T2 hyperintensity does not seem to discriminate between those that do well versus those that do not (18,21,22,53). This is partially due to its high prevalence.…”
Section: Conventional and Advanced Mrimentioning
confidence: 99%
“…It has also been shown that microstructural changes can be used to evaluate progression of the disease, and outcome (7,26,27). Recent studies suggested that patients with an FAvalue >0.55 represent the best responders to surgery at 1-year (27,53). Additional advanced MRI techniques such as magnetization transfer, T2* and spectroscopy as well as others, are also promising techniques that remain the subject of ongoing investigations (28).…”
Section: Conventional and Advanced Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…The editors of the issue contributed to this introductory review and decided to limit each of the past, present, and future sections to three themes in an effort to stay focused on the most important topics. The remaining 11 articles included 9 research papers and 2 systematic reviews focusing on different aspects, ranging from genetic factors [ 6 ] to clinical assessments [ 7 , 8 ], imaging [ 9 , 10 ], sagittal balance [ 11 ], surgical treatment [ 12 ], and outcome prediction [ 13 , 14 , 15 , 16 ] ( Table 1 ). These articles represented contributions from a diverse group of researchers coming from multiple countries, including Switzerland, Germany, Italy, United Kingdom, United States, South Korea, and Canada.…”
mentioning
confidence: 99%